METHODOLOGICAL APPROACHES IN INFORMATICS PREPARATION FOR WORKING WITH MASS MEDIA - Turganbaeva, А.Р.; Kanatbekova, А.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Now, along with the development of various information technologies, it is impossible to cover the number of systems for training competitive specialists at the university, which is offered for the useful education of young people, teaching theory in combination with various technologies. The use of various information technologies also requires knowledge of the use of electronic media from a modern computer science teacher, while there is no training methodology for this aspect. The purpose of the article is to further improve the training of bachelors of computer science by identifying the target interests and positions of students through the disclosure of the role of electronic media in the use of information technologies. The article proposes methodological approaches to improve the organization of educational and research activities of future computer science teachers when working with electronic media. In the course of the study, an elective course "Electronic Mass Media" was developed, the content of the course and the study guide of the same name were selected, which, in addition to theoretical material, included practical tasks and questions to consolidate the material.